STUDY OF ELECTROCHEMICAL PROPERTIES OF COPPER IN SOLUTION OF SULPHURIC ACID WITH COPPER (II) IONS AND TITAN THROUGH POTENTIODYNAMIC POLARIZED CURVE - Bayeshov Abduali; Abizhanova Dinara; Abduvaliyeva Umida; Zhurinov Murat (Scientific Journal of Pedagogy and Economics, 2019)
The electrochemical properties of copper, titanium in sulfuric acid and their ions in aqueous solution are investigated in the potentiodynamic mode by the method of polarization curves. Electrochemical properties of copper and titanium electrodes in a solution of sulfuric acid involving copper (ІІ) ions and titanium with variable valency by means of potentiodynamic polarization curves. The recovery of copper (II) ions and the regularity of dissolution of the electrodes are determined. The reduction wave of tetravalent titanium ions in a solution of sulfuric acid with copper and titanium electrodes is registered for the first time in the polarization program, and it is indicated that the reduction wave of trivalent titanium ions in the above electrodes is not registered. It is also determined that when copper (II) ions are present in the electrolyte composition, the reduction wave of tetravalent titanium ions in the polarization curve is not registered. It is known that obtaining the main part of copper powders is performed by electrochemical method [1-12].